Using organisational role theory and job analysis to identify and define the roles of an effective Australian general practice supervisor. Issue 4 (4th July 2022) - Clement, Tim; Ingham, Gerard; Willems, Julie
ABSTRACT: General practice (GP) supervisors – the key resource for training the future GP workforce – are often described as 'occupying a role' or enacting a series of roles. However, as much of the discourse uses a lay understanding of role, or merely hints at theory, a significant body of theoretical literature is underutilised. We reasoned that a more rigorous application of role theory might provide a conceptually clearer account of the GP-supervisor's job. To this end, we describe the use of organisational role theory and job analysis to identify and define the roles of the Australian GP-supervisor. Our search of the academic literature identified 64 role titles, which we condensed to an initial iteration of core roles, using inclusion and exclusion criteria. We analysed GP training organisations' documents to map embedded supervisory tasks against our list of roles to verify their presence, review our role titles and definitions, and look for additional roles that we may have missed. We used subject matter experts iteratively, to authenticate a final list of ten roles and their accompanying definitions, which can be used to support Australian GP-supervisors to perform effectively. We encourage those who support GP-supervisors in other countries and those who educate other health professionals in primary care settings to review the roles to judge whether they are transferable to their contexts.